2020
DOI: 10.3389/fneur.2020.00408
|View full text |Cite
|
Sign up to set email alerts
|

Association of LDL-C/HDL-C Ratio With Stroke Outcomes Within 1 Year After Onset: A Hospital-Based Follow-Up Study

Abstract: Stroke remains a leading cause of death and disability. The low-density lipoprotein cholesterol to high-density lipoprotein cholesterol (LDL-C/HDL-C ratio) ratio has been confirmed to be a predictor of stroke. However, few studies have assessed the prognostic impact of the LDL-C/HDL-C ratio for stroke patients. We aimed to investigate the relationship between the LDL-C/HDL-C ratio and the prognosis following stroke in Chinese patients. A total of 3,410 patients who had experienced their first ischemic stroke w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 26 publications
(26 reference statements)
0
28
0
2
Order By: Relevance
“…In contrast, You et al [9] included 356 patients with intracranial hemorrhage (mean age 64.1 ± 13.7 years, mean follow-up =0.22 years) and found that the LDL-C/HDL-C ratio was negatively correlated with all-cause mortality, they suggested that the LDL-C/HDL-C ratio should be controlled above 2.96. Liu et al [10] recruited 3250 stroke patients (mean age 63.72 ± 11.33 years, mean follow-up =1.00 years) and found a negative relationship between the LDL-C/HDL-C ratio and all-cause mortality. Mortality was lowest when the LDL-C/HDL-C ratio was between 2.23 and 2.88.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, You et al [9] included 356 patients with intracranial hemorrhage (mean age 64.1 ± 13.7 years, mean follow-up =0.22 years) and found that the LDL-C/HDL-C ratio was negatively correlated with all-cause mortality, they suggested that the LDL-C/HDL-C ratio should be controlled above 2.96. Liu et al [10] recruited 3250 stroke patients (mean age 63.72 ± 11.33 years, mean follow-up =1.00 years) and found a negative relationship between the LDL-C/HDL-C ratio and all-cause mortality. Mortality was lowest when the LDL-C/HDL-C ratio was between 2.23 and 2.88.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies on the LDL-C/HDL-C ratio have drawn inconsistent conclusions. Some studies have suggested that the LDL-C/HDL-C ratio is positively associated with CVD [5][6][7][8], while others have found a negative correlation between the LDL-C/HDL-C ratio and all-cause mortality [9,10]. The reasons for these inconsistencies can be attributed to differences in the study population, follow-up, and study endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, You et al [9] included 356 patients with intracranial hemorrhage (mean age 64.1 ± 13.7, mean follow-up years = 0.22) and found that LDL-C/HDL-C ratio was negatively correlated with all-cause mortality, and considered that LDL-C/HDL-C ratio should be controlled at more than 2.96. Liu et al [10] recruited 3,250 stroke patients (mean age 63.72 ± 11.33, mean follow-up years = 1.00) for analysis and found a negative relationship between LDL-C/HDL-C ratio and all-cause mortality, mortality was lowest as LDL-C/HDL-C ratio was between 2.23 and 2.88. The above studies suggest that the relationship between LDL-C/HDL-C ratio and all-cause mortality may be negative, and propose an inconsistent optimal range of LDL-C/HDL-C ratio.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies on LDL-C/HDL-C ratio have inconsistent conclusions. Some studies have suggested LDL-C/HDL-C ratio was positively associated with CVD [5][6][7][8], while others have found a negative correlation between LDL-C/HDL-C ratio and all-cause mortality [9,10]. The reasons for these inconsistencies can be attributed to differences in the study population, follow-up, and study endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…These lipoproteins have been recommended for screening people with a high risk of NAFLD in clinical practice [18]. Recently, some studies have pointed out that the LDL/HDL cholesterol ratio can simultaneously evaluate LDL cholesterol and HDL cholesterol, and its performance in predicting the risk of cardiovascular and cerebrovascular metabolic-related diseases is better than that of a single lipoprotein [19][20][21]. At present, there are no research data on the association between NAFLD and the LDL/HDL cholesterol ratio.…”
Section: Introductionmentioning
confidence: 99%